Competition and risk-taking - Oliver Gürtler; Lennart Struth; Max Thon (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In many situations, agents take risks by choosing an action that increases their performance immediately, but that potentially leads to a large loss. The current paper studies how such risk-taking behavior depends on the level of competition that the agents face. We study a tournament model and we find that more intense competition, measured by the number of competitors as well as their relative standing, induces agents to take higher risks. We use a rich panel data set on professional biathlon competitions as well as survey data from professional biathletes to confirm the model predictions. Finally, we discuss implications for organizational decision-making.
Keywords: M51; M52; Z22; 330; Risk-taking; competition; tournament; incentives; biathlon